Estudo Retrospectivo da Doença de Chagas em doadores de sangue daregião noroeste do Rio Grande do Sul, Brasil - Pedroso, Débora (2012)
Chagas Disease was discovered by Carlos Chagas in 1909. It is an hematological and tissue infection caused by flagellate protozoan Trypanosoma cruzi, which is transmitted by an hematophagous insect. In addition to transmission by the vector this parasitic infection can be acquired by humans in other ways, such as blood transfusion, laboratory accidents, organ transplants, oral transmission by penetration of trypomastigotes through oral mucosa or through placenta. Although blood transmission shows a decline after implementation of donor screening this is still present, and therefore needs constant vigilance. In view of this, the study aims to describe from a retrospective analysis a serological profile for Chagas disease in blood donors from the municipality of Santiago located in the northwestern state of Rio Grande do Sul, in which high levels of endemic disease appeared in past decades. The results of serological blood donors from the Blood Bank of municipality of Santiago were analyzed during the period 2001-2011. Of the 10,164 units of blood collected, with an average of 1,016 units per year, 2.68% were reactive to T. cruzi, being the main cause of discarding blood bags. The higher frequency of positive cases occurred in men, with mean age of 38.84 years old, coming from the urban area of the municipality of Santiago. Regarding the positive cases among women, 25% were younger than 31 years old. From these results, an expressive serum reactivity to T. cruziamong donors in this region could be noticed during the study period, more frequently in men over thirty years old. Although serological screening detects the majority of cases positive for Chagas disease, it does not make impossible transmission via transfusion. Therefore it is important to devise epidemiological strategies to determine the main form of infection that is occurring in the region.